2020
DOI: 10.21203/rs.3.rs-39095/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploratory study of risk factors for congenital malformations in Morocco

Abstract: Background: The aim of the study is to describe the teratogenic risk factors of congenital malformations in a large sample from the Moroccan population.Methods: It is a descriptive epidemiological study conducted between January 1st, 2011 and June 31th, 2016 at the "Les Orangers" maternity and reproductive health hospital in Rabat, Morocco.The data were collected on pre-established sheets and on the hospital’s malformations register.Results: A total of 245 cases of congenital malformations were recorded out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This study reported a prevalence of congenital malformations of 9.2 per 1000 births, a figure that aligns closely with those reported in other parts of Morocco: 1.02% of a percent at the Souissi maternity hospital in Rabat (25), 1.34% in the Oriental region (26), and 5.58 per 1000 at the "Les Orangers" hospital in Rabat (27). Comparatively, in other African countries, the prevalence stands at 9 per 1000 births in Cameroon (28), 3.2 per 1000 in Togo (29), and 3.6 per 1000 in Ivory Coast (30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study reported a prevalence of congenital malformations of 9.2 per 1000 births, a figure that aligns closely with those reported in other parts of Morocco: 1.02% of a percent at the Souissi maternity hospital in Rabat (25), 1.34% in the Oriental region (26), and 5.58 per 1000 at the "Les Orangers" hospital in Rabat (27). Comparatively, in other African countries, the prevalence stands at 9 per 1000 births in Cameroon (28), 3.2 per 1000 in Togo (29), and 3.6 per 1000 in Ivory Coast (30).…”
Section: Discussionsupporting
confidence: 89%
“…In our series, poly malformation syndrome was observed in 22.64% of cases, a figure nearly identical to that reported by the "Les Orangers" hospital in Rabat, where the syndrome was present in 26.5% of cases (27). Regarding the prevalence distribution of the various malformations identified in our study, neural tube malformations emerged as the most prevalent, with a frequency of 39.62%, followed by musculoskeletal malformations at 26.4%.…”
Section: Discussionsupporting
confidence: 88%